Hepatocellular Carcinoma in Asia: A Challenging Situation - Jafri, Wasim (Euroasian J Hepatogastroenterol, 2019)
Amongst the primary tumors of the liver, hepatocellular carcinoma (HCC) is the most common. It is also one of the most prevalent types of cancers in Asia. Mostly, HCC occurs on a background of chronic liver disease and liver cirrhosis; however, de novo HCCs can also arise in apparently normal looking livers on imaging. There are multiple risk factors for HCC, including hepatitis B and C infections, diabetes mellitus, alcohol, and nonalcoholic steatohepatitis. Other common risk factors which are known to be involved in the pathogenesis of HCC are obesity, food contaminated with aflatoxin and hemochromatosis. Many of these factors are commonly found in this part of the world, hence the high burden of disease. Besides these, smoking and familial predisposition to HCC also seem to have an important role to play in its development. Majority of HCC are missed at an early stage despite the emphasis on adequate screening and surveillance strategies. Therefore, most of the time these tumors are diagnosed at a fairly advanced stage, when palliative treatment is the only therapeutic option left. Hence, prevention of HCC by controlling and minimizing the possible risk factors is the need of the hour. How to cite this article: Jafri W, Kamran M. Hepatocellular Carcinoma in Asia: A Challenging Situation. Euroasian J Hepatogastroenterol 2019; 9(1):27-33.